The effects of six weeks of Core stabilization exercise on pain, Functional disability and Isometric strength of the trunk and lower extremities Muscle in women with patellofemoral pain syndrome - Karami Keshmarzi, Shirin; Gheitasi, Mehdi; Miri, Hadi (Advances in Nursing & Midwifery, 2018)
Abstract Background and Aim: The knee joint is most common of region for injury and musculoskeletal disorders in lower extremity. Patellofemoral pain syndrome is as a common cause of knee pain in subjects. The purpose of present study was to assess the effect of core stabilization exercises on pain, functional disability andstrength of muscles of thelower Extremity and trunk in females with patellofemoral pain syndrome. Materials and Methods: Subjects in this study were 20 female with patellofemoral pain syndrome participated. The subjects were randomly divided into two groups. 10 Subjects in the experimental group (age 32.13±1.95 yr, height 169.00±7.59 cm, weight 65.50±6.80 kg) and 10 Subjects in the control group (age 31.25±1.58 yr, height 170.00±7.46 cm, weight 67.50±14.39 kg) participated in this study. Then experimental group performed exercises for 6 weeks. The Visual Analogue Scale (VAS) and Western Ontario and McMaster Universities (WOMAC) questioners were used to measure rate of functional disability and pain pre and post six weeks in both groups. also was used the dynamometer for measure isometric strength pre and post six weeks. Data using descriptive and inferential statistics (independent t test to compare scores at pre-test and post hoc t test to compare pre- and post-test scores) were analyzed. Results: The results showed that Core stabilization exercises has a significant effect on pain reduction in experimental compared with control group (p= 0.003). The mean score of disability test also showed significant improvement in experimental compared with control group (p= 0.001). Also, the results showed that Isometric strenghtening trunk flexor (p= 0.005) and extensor (p= 0.036), hip flexor (p= 0.001) and extensor (p= 0.001), hip abductor (p= 0.001) external rotator (p= 0.019), knee flexor (p= 0.001) and extensor muscles (p= 0.001) improved significantly compared with control group. Conclusion: According to results of this study, core stabilization exercises can reduce pain and improved disability and muscles isometric strength in subjects with patellofemoral pain syndrome.